Faktor - Faktor Yang Mempengaruhi Kinerja Pegawai (Studi Empiris Pada Satuan Kerja Berbentuk Badan di Pemkab Sragen) - Suradi, Suradi; , Dr. Triyono, M.Si; , Drs. M. Farid Wajdi, MM., Ph.D (2015)
This research purpose to reach: (1) to know transformational leadership influences on employee performance of regency government of Sragen (2) to know organizational communication influences on employee performance of regency government of Sragen (3) to know organizational commitment influences on employee performance of regency government of Sragen (4) to know job satisfaction influences on employee performance of regency government of Sragen. This research is association/correlation that purposes to know correlation among two or more variables. Sum variable in this research is 111 employees of regency government of Sragen. Analysis technique of this research uses instrument test is validity and reliability test. Analysis regression linier is normality, multicolinierity and heterocedasticity tests. Hypothesis test is coefficient determination, t test and F test. Result of this research shows (1) transformational leadership influences positive on employee performance according to t test is significance (2) organizational communication influences positive on employee performance according to test is significance. (3) Organizational commitment influences positive on employee performance according to t test is significance (4) job satisfaction influences positive on employee performance according to t test is significance. Implication of this research is the other researcher to research other work division else board form. The other analysis of research is analysis regression with moderating variable or SEM analysis, analysis factor or the other analysis. The other research adds area research so the research consist some regencies.